An alternative finance system against a secret threat of conventional banks: pool finance economics system - Kayadibi, Saim (s.n, 2012)
This paper aims at critical examination of the Pool Finance Economic System (PFES). As it is known that usury (riba) basically is a making money method from money without encountering a risk and an effort. Conventional banks offer loans to institutions of state in exorbitant interest rates with the collected loans from different institution of the same state in cheap interest rates. Therefore, the conventional banks augment their money without risk through lending an institution’s money to other sector of the same institution